Análise das conformidades dos portais de transparência das câmaras de vereadores dos municípios do Rio Grande do Sul - Techio, Jane Werle (2020)
The general objective of the present study aimed to demonstrate the degree of compliance, of the institutional sites of the bodies of the Legislative power of the municipalities of Rio Grande do Sul with more than 10 thousand inhabitants, according to the mandatory precepts recommended by Federal Law 12.527 / 2011, known as Law Access to Information (LAI). The study was conducted during the period 2019 and 2020, in a sample of 167 municipalities. An assessment was made of the websites of the Legislative Powers of the Municipalities of Rio Grande do Sul based on data from the years 2013, 2014, 2015, 2016, 2017 and 2018 collected on the website of the Court of Auditors of the aforementioned state. It was possible to conclude that after the enactment of law 12.527 / 11, the city councils of city councilors in the municipalities of the state of Rio Grande do Sul with more than 10,000 inhabitants, in general, have been evolving positively, albeit in a slow manner, with regard to compliance with the access to information law, giving public services more transparency as determined by the aforementioned legislation. It is also concluded that of the 167 municipalities studied over the six-year period 2018, 2017, 2016, 2015, 2014 and 2013, only 13.7% of these federated entities are classified as municipalities with a high or very high level of law enforcement of transparency, the remaining 86,3% are classified as legislative by municipalities of reasonable, low or very low level of compliance with LAI. Likewise, it is concluded that the municipality with the Legislative Branch that has the highest level of transparency in the sample studied is Bento Goncalves and the Legislative Branch that has the lowest level of transparency is the city of Planalto. Still conclusively, the functional region considered more transparent by COREDES RS is functional region 9 that covers the COREDEs Alto da Serra do Botucaraí, Middle Alto Uruguay, Northeast, North, Production and Rio da Várzea.